Analisis Kegiatan Praktikum Biologi SMA Materi Sistem Pernapasan Manusia: (Analysis of the Activities of the Biology Practicum in High School of Human Respiratory System Material) - Meirin Dwiningtyas Putri; Sri Anggraeni; Bambang Supriatno (BIODIK, 2020)
Student Worksheets (LKS) are used as a means or purpose to guide the implementation of teaching and learning activities and assist students in learning to be more directed towards practical activities. If the worksheets are arranged with good quality, the learning obtained by students will be of good quality too. This study aims to explain the results of the analysis, testing and reconstruction of the Human Respiratory System Worksheet used in SMA / MA Tasikmalaya and the subject of this study is the Student Worksheet (LKS) of the Human Respiratory System. The research method used was qualitative descriptive method with a total of 6 samples. The sampling technique using total sampling. This study uses instruments developed by the Lecturer TEAM namely conceptual analysis rubric, practical analysis rubric, and knowledge construction rubric as well as instruments based on scoring tables of the Vee Diagram component adapted by Novak & Gowin (1984). The results showed that still in terms of 1) conceptual, not in accordance with the demands of the Basic Competence curriculum 2) practical, the title / goal is not in accordance with the work steps and difficult to execute and not relevant to the objects / phenomena that arise 3) the construction of knowledge, the question has not led to the facts that arise, are not connected with the interpretation of the data and the conclusions that are built do not describe the title / purpose of the practical laboratory. Most of the worksheets have met the Diagram Vee component but have not yet met the maximum score so the quality needs to be improved. Therefore LKS Human Respiratory System still needs to be improved in terms of conceptual, practical and knowledge construction. Abstrak. Lembar Kerja Siswa (LKS) dijadikan sebagai sarana atau acuan untuk memandu pelaksanaan kegiatan belajar mengajar dan membantu siswa dalam belajar agar lebih terarah terutama pada kegiatan praktikum. Apabila LKS yang disusun dengan kualitas baik maka pembelajaran yang didapat siswa akan berkualitas baik pula. Penelitian ini bertujuan untuk menjelaskan hasil analisis, ujicoba dan rekonstruksi LKS Sistem Pernapasan Manusia yang digunakan di SMA/MA Tasikmalaya dan subjek penelitian ini adalah Lembar Kerja Siswa (LKS) Sistem Pernapasan Manusia. Metode penelitian yang digunakan adalah metode deskriptif kualitatif dengan sampel penelitian berjumlah 6 sampel. Teknik sampling dilakukan secara total sampling. Penelitian ini menggunakan instrumen yang dikembangkan oleh TIM Dosen yaitu rubrik analisis konseptual, rubrik analisis praktikal, dan rubrik analisis kontruksi pengetahuan serta dan instrumen berdasarkan tabel penskoran komponen Diagram Vee yang diadaptasi Novak & Gowin (1984). Hasil penelitian menunjukkan bahwa masih dalam hal 1) konseptual, belum sesuai dengan tuntutan Kompetensi Dasar kurikulum 2) praktikal, judul/tujuan belum sesuai langkah kerja dan sulit dieksekusi serta tidak relevan dengan objek/fenomena yang muncul 3) kontruksi pengetahuan, pertanyaan belum mengarahkan pada fakta yang muncul, tidak dihubungkan dengan interpretasi data serta kesimpulan yang dibangun belum menggambarkan judul/tujuan praktikum. Sebagian besar LKS sudah memenuhi komponen Diagram Vee namun belum memenuhi skor maksimum sehingga kualitasnya perlu ditingkatkan. Oleh karenanya LKS Sistem Pernapasan Manusia masih perlu diperbaiki dari segi konseptual, praktikal dan kontruksi pengetahuan.